8 - Des discours aux pratiques du développement en Afrique : une réflexion sur la problématique du développement local dans le milieu rural Toura (Côte d’Ivoire1): https://doi.org/10.4314/ad.v34i1.57361 - Soumahoro, Moustapha (Africa Development, 2009)
Local development may be defined as the capacity of a society to deal with current issues at hand. It may also be referred to as the process by which a population acquires the means of mobilizing its productive forces in transforming its environment in order to improve the living conditions of its constituents. Therefore, as discussions arise on local development, some may find coalescence on the epistemological, theoretical, methodological and practical approaches; as well as a resolve on the causes, objectives and final results. In reality, the practice of local development is much more complex, as this article proposes, following discussions with local citizens, community and associative representatives from the Toura area of the Ivory Coast. The goal is to study the feedback from experi- ments of local development which are in progress in the region of Toura. Empha- sis will then be placed on the thought-process of the local development, the knowledge of the Toura area in general, and the socio-economic contexts in order to improve the conditions of the true development. This will in turn present some strategies to be applied which will be articulated around an accommodation of the standards, practices and structures traditional with the profit of modernization.